Life Within the Kosi Embankments - Mishra, Dinesh Kumar (Water Nepal, 2003)
In 1954 governments of Nepal and India signed the Kosi agreement paving way for the implementation of the Kosi embankments to control its floods. Known for its vagaries the river had shifted its course for about 115 kilometres in past 200 years. Though the embankments were meant to provide security from flooding, today large tracks of land, higher than that expected to be made secure from flooding by the embankment, lie waterlogged in Kosi dependent region of north Bihar. This paper documents lessons of implementing a large-scale structural approach i.e. embankment, in a densely populated alluvial landscape. The implementation of the embankments was fraught with human miseries that remained unheeded as technical hubris intermixed with the imperatives of project implementations. More than 200,000 people live within the Kosi embankments and cope with the consequences of the interventions expected to provide them security from annual flooding. Conventional policy science to flood control remains insulated from the consequences of its interventions, while the hapless communities have become despondent. Water Nepal Vol. Vol.9-10, No.1-2, 2003, pp.277-301